(untitled) (Revista Electrónica REDINE, 2021)
This review describes the process of creation and consolidation of the REVISTA VENEZOLANA DE SALUD PUBLICA (RVSP) (ISSN: 2343-5526), a means of scientific dissemination of open access, refereed and indexed, attached to the Dean of Health Sciences of the University Centroccidental Lisandro Alvarado (UCLA), Venezuela. It publishes, disseminates and promotes research articles in the field of public health, especially in three major areas of interest such as health management, health problems, disease of the population, and health promotion and prevention, this being its thematic focus. Founded in 2013 and published biannually, RVSP is indexed in Imbiomed, Doaj, Dialnet, Redib, Revencyt, Periódica, Latindex Catalogo and Amelica.